Implementasi Metode Analytical Network Process (ANP) Pada Sistem Pendukung Keputusan Dalam Seleksi Atlet Penyandang Disabilitas Sumatera Utara Untuk Bertanding Di Ajang Pekan Paralimpiade Nasional (PEPARNAS) - Tafonao, Firdaus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
National Paralympic Week (Peparnas) is a competition event that resembles the National Sports Week (PON) for athletes with disabilities in Indonesia. At the National Paralympic Week (Peparnas) North Sumatra Province also registered athletes with disabilities to be able to compete to become champions at the event. In order to achieve the main goal of being a champion at the National Paralympic Week (Peparnas) it is necessary to need competent athletes with disabilities. Therefore, an appropriate selection process for athletes with disabilities is carried out by involving several established criteria. In this study the authors conducted research at the Medan City Youth and Sports Office to obtain the data needed for the selection procedure for athletes with disabilities in North Sumatra to compete at the National Paralympic Week (Peparnas). The purpose of this study is to design a decision support system for the selection of athletes with disabilities in North Sumatra using the Analytic Network Process (ANP) method. The system that has been designed can make it easier for the Medan City Youth and Sports Office to conduct the selection process for good and competent athletes with disabilities to be registered at the National Paralympic Week (Perparnas) competition. Where the results of the application of ANP, based on the evaluation results, the alternative that has the highest priority weight is the Foggia i alternative. Therefore, Foggia was chosen as Tamping at Tanjung Gusta Medan. Randi has a priority weight of 1.62